Method for condensing carbonyl structure based on boron-nitrogen compound
By introducing carbonyl groups directly onto boron-nitrogen compound molecules, a fused carbonyl structure synthesis method has been developed, which solves the problems of low synthesis efficiency and insufficient safety of carbonyl boron-nitrogen compounds in the prior art. This method achieves efficient and safe carbonylation reactions, expands the MR-TADF material library, and improves the performance of OLEDs.
Patent Information
- Application Number
- CN202511029460.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-10-31
AI Technical Summary
Existing methods for synthesizing carbonyl boron nitrogen compounds suffer from low yields, limited substrate range, complex operation, and insufficient safety. There is an urgent need for a new method that is more efficient, milder, and more universal.
A method based on the fused carbonyl structure of boron-nitrogen compounds was adopted. The reactants were reacted with titanium tetrachloride in a specific solvent, followed by extraction, drying and purification to obtain boron-nitrogen compounds with fused carbonyl structures. This method avoids high-risk conditions such as highly active organolithium and high-pressure carbon monoxide, and simplifies the synthesis process.
This method enables the direct introduction of carbonyl groups onto boron-nitrogen compound molecules, expands the molecular library of multiple resonance thermally activated delayed fluorescence materials, improves synthesis efficiency and safety, simplifies purification steps, and modulates photochromic and photophysical properties. The resulting organic electroluminescent devices exhibit high efficiency and high color purity.
Smart Images

Figure CN120865268A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic electroluminescent materials technology, and particularly relates to a method for fused carbonyl structures based on boron nitrogen compounds. Background Technology
[0002] Organic light-emitting diodes (OLEDs), as a class of self-emissive devices based on organic semiconductor materials, have demonstrated outstanding advantages in next-generation displays and solid-state lighting due to their backlight-free operation, thinness and flexibility, adaptability to curved displays, high contrast, wide viewing angle, and excellent color saturation. Compared with traditional liquid crystal displays, OLEDs not only have lower power consumption and faster response times, but also meet the diverse application needs of smart terminals, ultra-high-definition displays, automotive electronics, and wearable devices, becoming a core driving force for display technology innovation. To further improve the efficiency, color purity, and stability of blue light devices, carbonyl-based boron-nitrogen conjugated compounds have become an important research direction for multi-resonance thermally activated delayed fluorescence (MR-TADF) materials in recent years. B / N doping can form spatially separated frontier orbitals in the molecular framework, effectively reducing the singlet-triplet bandgap (ΔE). ST This achieves high efficiency in triplet exciton utilization; the introduction of the carbonyl group further enhances electron acceptor capability and molecular rigidity, reduces geometric relaxation loss, and provides... The composition of the state is used to accelerate reverse intersystem crossing (RISC). This collaborative molecular design strategy enables the material to simultaneously possess high efficiency, narrow bandwidth, and high color purity blue light emission characteristics, providing a new approach for the development of high-performance and stable OLEDs.
[0003] Currently, the methods for synthesizing carbonyl boron nitrogen compounds are very limited, and most of them have significant experimental limitations. Existing strategies mainly include the following categories: (1) Using dihydroacridine as a precursor, first construct a boron nitrogen compound containing methylene groups, and then oxidize it with DDQ to obtain the target carbonyl product. This method has a low yield and is highly dependent on specific substrates, which leads to strict limitations on the introduction position of the carbonyl group. (2) Using halogen-substituted boron nitrogen compounds, react with dry ice in the presence of organolithium reagents to generate acetic acid derivatives, and then dehydrate to obtain the carbonyl product. This route is complicated and involves highly active organolithium reagents, resulting in poor experimental safety. (3) Although the strategy of converting ester groups to carboxylic acids and further dehydrating to form carbonyl groups is feasible, ester groups are extremely unstable under typical synthetic conditions of boron nitrogen compounds (such as the presence of organolithium or boron tribromide). Therefore, it is usually necessary to first introduce carbonyl groups and then react with boron sources to form a boron skeleton containing three B–C bonds. However, the carbonyl group is also easily destroyed under the above conditions, and it needs to be reduced before it can react with the boron source, and finally oxidized to obtain the target carbonyl product, making the overall synthesis process lengthy and inefficient. (4) In the presence of a palladium catalyst, boron nitrogen compounds react directly with carbon monoxide under high pressure to generate carbonyl derivatives. Although this method is simple, it has strict requirements for equipment and requires the use of highly toxic carbon monoxide, which poses a high safety risk.
[0004] In summary, existing methods for synthesizing carbonyl boron nitrogen compounds generally suffer from problems such as low yield, limited substrate range, complex operation, and insufficient safety. There is an urgent need for a new method that is more efficient, milder, and more universal. Summary of the Invention
[0005] To address the problems existing in the background art, the present invention provides a method for fused carbonyl structures based on boron-nitrogen compounds, the process of which is as follows: The reactants and 1,1-dichloromethyl ether were dissolved in the reaction solvent. After cooling the solution to -70℃ to 0℃, titanium tetrachloride was added under a nitrogen atmosphere. The mixture was stirred at 25℃ to 120℃ for 2h to 24h. After the reaction was completed, a quencher was added to quench the reaction, and the mixture was extracted three times with an extractant. Then it was dried with a drying agent. The crude product was purified by silica gel column chromatography to obtain a boron nitrogen compound with a fused carbonyl structure. The reaction solvent is selected from o-dichlorobenzene, chlorobenzene, tert-butylbenzene, o-xylene, toluene, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,4-dioxane, ethyl acetate / chloroform, dichloromethane, acetone or diethyl ether; The quenching agent is selected from sodium carbonate, sodium bicarbonate, potassium carbonate, sodium hydroxide, or potassium hydroxide; The extractant is selected from dichloromethane / water or ethyl acetate / water; The desiccant is selected from anhydrous magnesium sulfate, anhydrous calcium chloride, or phosphorus pentoxide; The eluent used in the purification is selected from petroleum ether / ethyl acetate = 6-12:1 or petroleum ether / dichloromethane = 4-8:1; The molar ratio of the reactants, 1,1-dichloromethyl ether, and titanium tetrachloride is 1:1.2-8:1.4-10; The ratio of the reaction solvent to the reactants is 3 ml-20 ml: 1 mmol; The reactants have a structure having the following general formula I or general formula II: ; The boron-nitrogen compound with the fused carbonyl structure has a structure having the following general formula III or general formula IV: ; Among them, ring A is selected from C6~C 30 aryl, C5~C 30 heteroaryl groups; This indicates whether a single key connection exists or no key connection exists here; R may be the same or different, and each is independently selected from hydrogen, C1~C1. 12 Alkyl groups, C6~C 18 aryl, C2~C 18 The heteroaryl group; X is selected from S=O, S(=O)2, C=O, O, S or Se, or from CR1R2 or NR3; R1, R2, and R3 are each independently selected from deuterium, halogen, cyano, substituted or unsubstituted C1~C. 12 Chain alkyl, substituted or unsubstituted C3~C 10 cycloalkyl, substituted or unsubstituted C6~C 30 arylamine, substituted or unsubstituted C3~C 30 heteroarylamine, substituted or unsubstituted C6~C 30 aryl, substituted or unsubstituted C2~C 30 One of the heteroaryl groups; When substitution is present, the substituents are each independently selected from halogens, cyano groups, and C1~C6 groups. 12 Chain alkyl groups, C3~C 10 cycloalkyl, C6~C 30 arylamine, C3~C 30 heteroarylamine, C6~C 30 Aryl, C2~C 30 One or more of the heteroaryl groups.
[0006] As a preferred embodiment of the present invention, the reaction solvent is o-dichlorobenzene.
[0007] As a preferred embodiment of the present invention, the solution is cooled to 0°C.
[0008] As a preferred embodiment of the present invention, the mixture is stirred at 50°C for 4 hours.
[0009] As a preferred embodiment of the present invention, the quenching agent is sodium carbonate.
[0010] As a preferred embodiment of the present invention, the extractant is dichloromethane / water.
[0011] As a preferred embodiment of the present invention, the desiccant is anhydrous magnesium sulfate.
[0012] As a preferred embodiment of the present invention, the eluent is petroleum ether: ethyl acetate = 8:1.
[0013] As a preferred embodiment of the present invention, the molar ratio of the reactants, 1,1-dichloromethyl ether, and titanium tetrachloride is 1:1.2:1.4; and the molar relationship between the reaction solvent and the reactants is 4 ml:1 mmol.
[0014] The beneficial effects of this invention are as follows:
[0015] The present invention provides a method for fused carbonyl structures based on boron-nitrogen compounds. This method involves fused a carbonyl group that influences the frontier molecular orbital energy levels and electron cloud distribution of a boron-nitrogen compound. This electron-withdrawing group can be directly introduced into the HOMO site of the boron-nitrogen compound molecule, forming a B / N / C=O system that can be applied to organic electroluminescent devices. This system expands the molecular library of multiple resonance thermally activated delayed fluorescence (MR-TADF) materials, providing a foundation for designing more commercially viable thermally activated delayed fluorescence OLED materials in the future. By using a simple, efficient, mild and easy-to-process one-step carbonylation reaction, an electron-withdrawing carbonyl lock is strategically introduced into the para position of the nitrogen atom in the boron-nitrogen compound skeleton. This method avoids high-risk conditions such as organolithium, high-pressure environment and carbon monoxide, and has the advantages of high yield and few by-products, which significantly simplifies the purification steps. Furthermore, this strategy can directly modify the structure of existing boron-nitrogen compounds, thereby flexibly controlling their photochromic and photophysical properties, providing an efficient synthetic route for the development of novel luminescent materials. Compared with the parent molecule (reactant), the synthesized boron-nitrogen compounds with fused carbonyl structures not only reduce the intramolecular charge transfer intensity, thus causing a blue shift in the emission spectrum, but also suppress the structural relaxation of the excited state, thereby narrowing the emission spectrum. This has the effect of regulating the material's photochromic properties and narrowing the full width at half maximum (FWHM). Organic electroluminescent devices prepared using the synthesized boron-nitrogen compounds with fused carbonyl structures also achieve the goals of high efficiency and high color purity. Attached Figure Description
[0016] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 The C-NMR spectrum of CO-BCzBN; Figure 2 The NMR spectrum of CO-BCzBN is shown in the figure. Figure 3 The mass spectrum of CO-BCzBN; Figure 4 A physical image of CO-BCzBN; Figure 5 The C-NMR spectrum of CO-DABNA; Figure 6 The H-NMR spectrum of CO-DABNA; Figure 7 This is the mass spectrum of CO-DABNA; Figure 8 A picture of the actual product, CO-DABNA; Figure 9 A schematic diagram of the structure of the organic electroluminescent device fabricated for the device embodiment; Reference numerals: 1-glass substrate, 2-hole transport layer, 3-electron blocking layer, 4-light emitting layer, 5-electron transport layer, 6-cathode layer. Detailed Implementation
[0017] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0018] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents and instruments whose manufacturers were not specified were all commercially available products. Some reaction compounds were purchased from a supplier (Zhengzhou Alpha Chemical Co., Ltd.), while some compounds that could not be directly purchased were prepared from commercially available raw materials through simple reactions.
[0019] Synthesis Examples
[0020] Synthesis of CO-BCzBN:
[0021] ;
[0022] Reactant a (3.21 g, 5.0 mmol) and 1,1-dichloromethyl ether (0.69 g, 6.0 mmol) were dissolved in 20 mL of o-dichlorobenzene (o-DCB). After cooling the solution to 0 °C, titanium tetrachloride was added under a nitrogen atmosphere. (1.33 g, 7.0 mmol). The mixture was stirred at 50 °C for 4 h. After the reaction was complete, sodium carbonate was added to quench the reaction, and the mixture was extracted three times with dichloromethane / water, followed by anhydrous magnesium sulfate. The crude product was dried. It was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 8:1) to give CO-BCzBN (2,5,8,11-tetratert-butyl-16H-3a²,13b-diaza-6b-boronacenaphthene[1,2,3,4,5-pqrst]indeno[1,2,3-de]pentaphenyl-16-one), as an orange powder (1.33 g, 40%).
[0023] Product characterization: 1 H NMR (500 MHz, CD2Cl2) δ 8.94 (d, J = 1.9 Hz, 1H), 8.90 (d, J = 1.6 Hz, 1H), 8.71 (d, J = 9.0 Hz, 1H), 8.44 (s, 1H), 8.40 (d, J = 1.9Hz, 1H), 1.61 (s, 9H),1.57 (s, 9H). 13 C NMR (151 MHz, CDCl3) δ 178.01, 147.26, 146.54, 146.39,146.22, 145.34, 140.99, 138.95, 137.90, 137.71, 135.73, 132.96, 130.00,129.55, 127.42, 125.29, 124.73, 124.37, 124.00, 123.56, 123.36, 121.30,120.94, 119.68, 117.22, 116.00, 114.86, 109.22, 35.76, 35.54, 35.14, 34.88, 32.25, 32.05, 31.81. Synthesis of CO-DABNA: ; Reactant b (3.23 g, 5.0 mmol) and 1,1-dichloromethyl ether (0.69 g, 6.0 mmol) were dissolved in 20 mL of o-dichlorobenzene (o-DCB). After cooling the solution to 0 °C, titanium tetrachloride was added under a nitrogen atmosphere. (1.33 g, 7.0 mmol). The mixture was stirred at 50 °C for 6 h. After the reaction was complete, hydrochloric acid was added to quench the reaction, and the mixture was extracted three times with dichloromethane / water, followed by anhydrous magnesium sulfate. The crude product was dried. It was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 8:1) to give CO-DABNA (2,10,15-tri-tert-butyl-5-(4-tert-butylphenyl)-5,12b-diaza-16b-boronazonaphtho[1,2,3,4-rst]pentabenzene-8(5H)-one), as a light yellow powder (1.17 g, 35%).
[0024] Product characterization: 1 H NMR (500 MHz, CD2Cl2) δ 9.03 (d, J = 2.5 Hz, 1H), 8.86 (d, J = 2.4 Hz, 1H), 8.54 – 8.49 (m, 2H), 8.24 (d, J = 9.0 Hz, 1H), 8.16 (d,J = 9.0 Hz, 1H), 7.78 – 7.71 (m, 3H), 7.68 (ddd, J = 15.9, 9.0, 2.5 Hz, 2H), 7.36 (dd, J = 8.0, 2.5 Hz, 1H), 7.25 (dd, J = 8.1, 2.4 Hz, 1H), 6.97 (d, J =9.0 Hz, 1H), 6.74 (d, J = 9.1 Hz, 1H), 1.51 (d, J = 2.2 Hz, 18H), 1.49 (s,9H), 1.46 (s, 9H). 13C NMR (151 MHz, CD2Cl2) δ 177.72, 153.03, 149.31, 147.51,147.32, 145.54, 144.55, 143.44, 142.46, 139.71, 138.77, 131.81, 131.06,130.88, 130.18, 129.90, 129.26, 129.16, 128.65, 128.18, 127.94, 126.78,122.49, 122.44, 121.94, 118.52, 113.98, 111.43, 35.32, 35.08, 35.03, 34.85, 31.79, 31.72, 31.61, 31.52. In addition, it should be noted that other compounds in this application can be obtained by referring to the preparation methods of the examples listed above, so they will not be listed one by one here.
[0025] Device Examples
[0026] Preparation process: Substrate treatment: Immerse the ITO glass in a commercial glass cleaner (e.g., 2% Elma EC or equivalent) and ultrasonically treat for 20–30 minutes; then rinse thoroughly with deionized water to remove cleaning agent residue; next, ultrasonically clean the substrate in a mixture of acetone and ethanol, treating twice with each solvent for 10 minutes each time, to further remove oil and organic impurities; place the cleaned substrate in a clean oven and heat-dry at approximately 100°C for at least 30 minutes to ensure complete removal of surface moisture; after cooling to room temperature, treat with a UV / ozone cleaning system for 10 minutes to further enhance the hydrophilicity and hole injection capability of the ITO surface; finally, to further enhance the adhesion and interface quality of the organic layer, bombard the substrate surface with a low-energy ion beam (e.g., argon ions) to form a cleaner and more activated surface for subsequent organic layer deposition.
[0027] Vacuum evaporation was performed on the washed substrate to deposit each layer, and a cross-sectional view was prepared as shown below. Figure 9 The light-emitting area shown is 4mm. 2 Organic electroluminescent devices: First, the aforementioned substrate is introduced into a vacuum evaporation bath, and the pressure is reduced to 1 x 10⁻⁶. -5 Pa. Then, on the substrate, hole transport layer 2, light-emitting layer 3 and electron transport layer 4 are sequentially formed as organic compound layers, and then cathode layer 5 is formed.
[0028] A hole transport layer 2 was constructed using 60 nm thick vacuum-deposited 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC) and 10 nm thick vacuum-deposited 4,4',4” tris(carbazole-9-yl)triphenylamine (TCTA). A 30 nm thick vacuum-deposited mixture of 9-(2-(9-phenyl-9H-carbazole-3-yl)phenyl)-9H-3,9'-bicarbazole (PhCzBCz) and... CO-BCzBN was used as the light-emitting layer 3, and 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1”-terphenyl]-3,3”-diyl]dipyridine (TmPyPb) with a film thickness of 40 nm was vacuum-deposited as the electron transport layer 4. Each organic material was deposited using resistance heating. The heated compounds were vacuum-deposited at a deposition rate of 0.3-0.5 nm. Finally, a metal mask was configured orthogonally to the ITO stripes to form the film cathode 5.
[0029] The cathode layer 5 is a two-layer structure formed by vacuum evaporation of lithium fluoride and aluminum with film thicknesses of 1 nm and 100 nm, respectively. The thicknesses of each layer were measured using a stylus-type film thickness gauge (DEKTAK). The device was then sealed in a glove box with a nitrogen atmosphere containing water and oxygen concentrations below 1 ppm. The sealing was achieved using a glass sealing cap and the aforementioned epoxy UV-curable resin for the film-forming substrate (manufactured by Nagase ChemteX Corporation).
[0030] Device Evaluation: A direct current was applied to the fabricated organic electroluminescent device, and its luminescence performance was evaluated using a Spectrascan PR650 luminance meter. The current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescence characteristics, the CIE color coordinates (0.133, 0.141), external quantum efficiency (35.1%), and power efficiency (33.0 m / W) were measured as a function of applied DC voltage. This indicates that when the synthesized boron-nitrogen compound containing a fused carbonyl structure is used as a dopant in the organic electroluminescent device, the fabricated device achieves the goals of high efficiency and high color purity.
[0031] The above embodiments only list the effect data of devices made from a portion of the structures. This is a representative sampling test. Based on the experimental data, the overall data is not significantly different and can represent the effects of other unlisted structures.
[0032] Those skilled in the art will readily recognize that many modifications and variations can be made to this invention without departing from its spirit and scope. Therefore, it is contemplated that this invention covers the modifications and variations provided within the scope of the appended claims and their equivalents.
Claims
1. A method based on the fused carbonyl structure of boron-nitrogen compounds, characterized in that, The process of this method is as follows: The reactants and 1,1-dichloromethyl ether were dissolved in the reaction solvent. After cooling the solution to -70℃ to 0℃, titanium tetrachloride was added under a nitrogen atmosphere. The mixture was stirred at 25℃ to 120℃ for 2h to 24h. After the reaction was completed, a quencher was added to quench the reaction, and the mixture was extracted three times with an extractant. Then it was dried with a drying agent. The crude product was purified by silica gel column chromatography to obtain a boron nitrogen compound with a fused carbonyl structure. The reaction solvent is selected from o-dichlorobenzene, chlorobenzene, tert-butylbenzene, o-xylene, toluene, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,4-dioxane, ethyl acetate / chloroform, dichloromethane, acetone or diethyl ether; The quenching agent is selected from sodium carbonate, sodium bicarbonate, potassium carbonate, sodium hydroxide, or potassium hydroxide; The extractant is selected from dichloromethane / water or ethyl acetate / water; The desiccant is selected from anhydrous magnesium sulfate, anhydrous calcium chloride, or phosphorus pentoxide; The eluent used in the purification is selected from petroleum ether / ethyl acetate = 6-12:1 or petroleum ether / dichloromethane = 4-8:1; The molar ratio of the reactants, 1,1-dichloromethyl ether, and titanium tetrachloride is 1:1.2-8:1.4-10; The ratio of the reaction solvent to the reactants is 3 ml-20 ml: 1 mmol; The reactants have a structure having the following general formula I or general formula II: ; The boron-nitrogen compound with the fused carbonyl structure has a structure having the following general formula III or general formula IV: ; Among them, ring A is an aromatic ring selected from C6~C6. 30 Aryl, C2~C 30 Mixed aromatics; This indicates whether a single bond exists or not; R is the same or different, and each is independently selected from hydrogen, C1~C1. 12 Alkyl, C6~C 18 aryl, C2~C 18 The heteroaryl group; X is selected from S=O, S(=O)2, C=O, O, S or Se, or from CR1R2 or NR3; R1, R2, and R3 are each independently selected from deuterium, halogen, cyano, substituted or unsubstituted C1~C. 12 Chain alkyl, substituted or unsubstituted C3~C 10 cycloalkyl, substituted or unsubstituted C6~C 30 arylamine, substituted or unsubstituted C3~C 30 heteroarylamine, substituted or unsubstituted C6~C 30 aryl, substituted or unsubstituted C2~C 30 One of the heteroaryl groups; When substitution is present, the substituents are each independently selected from halogens, cyano groups, and C1~C6 groups. 12 Chain alkyl groups, C3~C 10 cycloalkyl, C6~C 30 arylamine, C3~C 30 heteroarylamine, C6~C 30 Aryl, C2~C 30 One or more of the heteroaryl groups.
2. The method based on the fused carbonyl structure of boron nitrogen compounds according to claim 1, characterized in that: The reaction solvent is o-dichlorobenzene.
3. The method based on the fused carbonyl structure of boron nitrogen compounds according to claim 1, characterized in that: The solution was cooled to 0°C.
4. The method based on the fused carbonyl structure of boron nitrogen compounds according to claim 1, characterized in that: The mixture was stirred at 50°C for 4 hours.
5. The method for fused carbonyl structures based on boron-nitrogen compounds according to claim 1, characterized in that: The quenching agent is sodium carbonate.
6. The method for fused carbonyl structures based on boron-nitrogen compounds according to claim 1, characterized in that: The extractant is dichloromethane / water.
7. The method for fused carbonyl structures based on boron-nitrogen compounds according to claim 1, characterized in that: The desiccant is anhydrous magnesium sulfate.
8. The method for fused carbonyl structures based on boron-nitrogen compounds according to claim 1, characterized in that: The eluent is petroleum ether: ethyl acetate = 8:
1.
9. The method for fused carbonyl structures based on boron-nitrogen compounds according to claim 1, characterized in that: The molar ratio of the reactants, 1,1-dichloromethyl ether, and titanium tetrachloride is 1:1.2:1.4; the ratio of the reaction solvent to the reactants is 4 ml:1 mmol.
Citation Information
Cited By
Boron-nitrogen-containing organic compound and organic electroluminescent device containing same
CN121064233A
